2021
DOI: 10.1002/cbin.11476
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR‐329‐3p sensitizes osteosarcoma cells to cisplatin through suppression of glucose metabolism by targeting LDHA

Abstract: Osteosarcoma (OS) is one of the most frequent malignant bone tumor types. Traditional treatments of OS involve standard chemotherapy or combination with radiation before and after surgery. Cisplatin is one of the most effective chemotherapeutic drugs used for treating osteosarcoma. However, patients with advanced tumor stages develop cisplatin resistance, leading to a major clinical challenge. In this study, we investigated the roles of miR‐329‐3p in cisplatin sensitivity of osteosarcoma cells. We found miR‐32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Selectively, shifting glycolysis to mitochondrial oxidation can suppress OS cell growth and metastasis [ 24 ]. Another study revealed that cisplatin-resistant OS cells showed enhanced glucose metabolism [ 25 ]. Additionally, 2-deoxy- d -glucose, a glycolytic inhibitor, could increase the sensitivity of OS cells to paclitaxel [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selectively, shifting glycolysis to mitochondrial oxidation can suppress OS cell growth and metastasis [ 24 ]. Another study revealed that cisplatin-resistant OS cells showed enhanced glucose metabolism [ 25 ]. Additionally, 2-deoxy- d -glucose, a glycolytic inhibitor, could increase the sensitivity of OS cells to paclitaxel [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…LDHA inhibition can significantly restore the sensitivity of chemotherapy drugs: LDHA knockdown sensitizes oral squamous cell carcinoma cells (122) and breast cancer cells (140) to Taxol and lung cancer cells to low doses of paclitaxel (141) via siRNA/shRNA. MiR-34a re-sensitizes colon cancer cells to 5-FU (142), miR-329-3p sensitizes osteosarcoma cells to cisplatin (143), and miR-7 sensitizes gastric cancer cells to cisplatin (144) all via LDHA inhibition. Recently, increasing studies have begun to explore LDHA inhibitors, which can be divided into three categories, represented by oxamate, 3dihydroxy-6-methyl-7-(phenylmethyl)-4-propylnaphthalene-1carboxylic acid(FX11), and N-hydroxyindoles (NHI) (145).…”
Section: Key Process Of Glycolysismentioning
confidence: 99%
“…Aerobic glycolysis allows the conversion of glucose into pyruvate eventually contributing to the production of lactate. This energy metabolic reprogramming promotes energy generation and thus facilitates OS cells proliferation, invasion, and chemoresistance [19]. Several factors including glycolytic enzymes (e.g., GLUT1), oncogenes (e.g., KRT17), transcription factors (e.g., HIF1α), tumor suppressors (e.g., p53), and related signaling pathways have been reported to regulate the glycometabolism in OS cells and play pivotal roles in overall survival of patients [20][21][22].…”
Section: Discussionmentioning
confidence: 99%